2010
DOI: 10.1590/s0100-72032010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Perfil clínico e microbiológico de mulheres com vaginose bacteriana

Abstract: RiCaRdo aRRaeS de aLenCaR XiMeneS 7 Artigo originalResumo OBJETIVO: estudar o perfil clínico e microbiológico de mulheres portadoras de vaginose bacteriana participantes de um ensaio clínico randomizado, duplamente mascarado, que comparou aroeira e metronidazol, em uso vaginal, para tratamento do corrimento genital. MÉTODOS: o estudo constitui-se em uma série de casos de 277 mulheres portadoras de vaginose bacteriana diagnosticada, concomitantemente, pelos critérios de Amsel e Nugent, selecionadas a partir de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
10

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
0
12
0
10
Order By: Relevance
“…The use of the pill as the contraceptive method most commonly reported among women, reinforce studies [6,16], which proves to be one of the most widely used, especially in northeast of Brazil. Research [25] on women's health in Brazil, showed that this type of contraception is one of the two most used methods.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The use of the pill as the contraceptive method most commonly reported among women, reinforce studies [6,16], which proves to be one of the most widely used, especially in northeast of Brazil. Research [25] on women's health in Brazil, showed that this type of contraception is one of the two most used methods.…”
Section: Discussionmentioning
confidence: 64%
“…This type of disease has been associated with lack of proper sexual orientation, education, hygiene habits, early onset of sexual activity and multiple partners [2,[8][9][10]. On the other hand, the disequilibrium in the vaginal ecosystem, due to the rise in pH above 4.5 and a decrease or absence of colonization by lactobacilli, decrease of vitamin A, folate and calcium may be predisposing factors to the proliferation of microrganismo [6,8,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the most frequent cause of genital discharge, responsible for 40 to 50% of the cases, and about half of the female carriers are asymptomatic. 10 Bacteria that inhabit the vagina are an important defense barrier of the body, representing a complex microbiological system, with about 109 bacterial colony forming units per gram of secretion and dozens of different species. Lactobacilli producing the hydrogen peroxide (H 2 O 2 ) show in vitro the ability to inhibit various bacteria, including Gardnerella vaginalis, anaerobes, Neisseria gonorrhoeae, among others.…”
mentioning
confidence: 99%